Pendekatan Computer Based Instruction (CBI) Dalam Implementasi Pembelajaran Interaktif Ilmu Shorof Dasar Berbasis Web - Ikasari, Diana; Samual, Syabira Syifa Syurafaa; Widiastuti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
Shorof is one of the branches of Arabic language studies that examines word formation changes (tashrif) to produce various meanings, focusing on how modifications in letters affect the meaning and function of words in sentences. This field is essential for those who want to understand Arabic in depth, especially in reading, writing, and interpreting the Quran. The study of Shorof is commonly conducted in Islamic boarding school (pesantren) or madrasah, often using memorization methods. However, this method is considered burdensome and time-consuming due to the repetition required, making it less effective. As a result, many people think that learning Shorof is difficult. By the advancement of digital technology, Shorof learning can be implemented through an interactive web based application using the Computer Based Instruction (CBI) approach as an alternative of media learning. This can assist learners in studying basic Shorof in a more modern way. The development of learning materials using the CBI approach focuses on drill and practice and tutorial models, which can be accessed via a website. The application is developed using the Bootstrap framework and programmed with PHP, HTML, CSS, JavaScript, and MySQL as the database. Through this interactive web-based learning platform, studying Shorof becomes more engaging for anyone interested in learning Arabic, while also making the learning process especially Shorof more accessible and effective.